Foregrounding the perspectives of mental health services users during the COVID-19 pandemic. Issue 3 (3rd July 2020) - Zeilig, Hannah; Gee, Brioney; Teague, Bonnie; Wilson, Jonathan; Hackmann, Corinna
Abstract : Purpose: This paper aims to highlight the critical importance of the perspectives of mental health service-users during the COVID-19 pandemic. Design/methodology/approach: This viewpoint is based on a review of recent research and literature and draws on consultations with experts by experience, including the lead author. Findings: The authors argue that expertise-by-experience is critical to policy, service development and research; but there is a risk it will be neglected at a time of rapid and reactive clinical development. Research limitations/implications: Understanding and responding to the nuances of individual need can only be achieved through coproducing service strategy design, delivery and research with mental health service users. The consultation outlined in this viewpoint gives some indication of the type of valuable insights that can be gained through seeking and listening to the perspectives of experts by experience. Originality/value: The discussions revealed that experience of managing severe and complex mental health conditions can actually be advantageous when facing a crisis such as COVID-19.